RANCANG BANGUN SISTEM INFORMASI POIN PELANGGARAN SISWA SMP WACHID HASYIM 7 SURABAYA MENGGUNAKAN FRAMEWORK CODEIGNITER - Kiswara, Anjung Adi; Syidada, Shofiya (Melek IT : Information Technology Journal, 2024)
Wachid Hasyim 7 Middle School Surabaya implements a violation point system as an effort to educate students' discipline. These violation points are used as a reference or basis for giving sanctions in the form of points. The implementation of this points system still faces several obstacles, including the process of recording points in a ledger by guidance and counseling teachers making it difficult to search for data and recap data on violation points. Apart from that, information about violations committed by students is often not conveyed to the student's parents, especially minor and moderate violations. This causes a gap in information about student delinquency between the school and the student's parents. Therefore, this research designs a website-based student violation point information system as a two-way information medium between the school and the student's parents regarding the acquisition of student violation points. This system development was made using the waterfall method. Implementation of system creation using the CodeIgniter framework with the PHP programming language and for database development using MySQL. This research succeeded in producing (1) an information system that makes it easier for schools to record and process data on student violations, (2) a system that can provide detailed information on student violations by adding photo evidence of violations, (3) a system that can provide information to guardians. students about student violations at school and allows for two-way communication with the school.